Anaerobic Baffled Reactor and Hybrid Anaerobic Baffled Reactor Performances Evaluation in Municipal Wastewater Treatment - Mohammad Aqanaghad (Iranian Journal of Health, Safety and Environment, 2018)
This work investigated the performance of an anaerobic baffled reactor (ABR) and a hybrid ABR (HABR) for the treatment of municipal wastewater (MWW) under ambient conditions and compared the ability of the two systems to meet effluent discharge standards. The reactors were studied under hydraulic retention times (HRTs) of 48, 36, and 24 hours and effluent recycling (ER) rates of 0.25-1. The startup success was determined by the COD removal efficiency. The startup lasted for 107 days. In steady state COD removal efficiency decreased from 91.4% using a 48-hour HRT to 83.5% using a 24-hour HRT in the ABR, while the COD removal efficiencies of the HABR were 2.2% greater than those of the ABR at all HRTs. The HABR met COD and BOD5 effluent discharge standards using a 36-hour HRT, while the ABR achieved these standards only with a 48-hour HRT. Using a 36-hour HRT, the HABR total nitrogen (TN) and total phosphorus (TP) removal efficiencies were 14.9% and 26.6%, while those of the ABR were 1.3% and 1% lower, respectively. The ABR and HABR met both the TSS and TP effluent standards using 48- and 36-hour HRTs, respectively, but neither met the TN effluent standard. ER did not have a positive effect on the total efficiency of either reactor. The HABR was found to be suitable for conventional MWW treatment, particularly in small cities and on-site treatment facilities.